2007
DOI: 10.1088/0741-3335/49/12b/s33
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic self organization, MHD active control and confinement in RFX-mod

Abstract: RFX-mod is a reversed field pinch (RFP) experiment equipped with a system that actively controls the magnetic boundary. In this paper we describe the results of a new control algorithm, the clean mode control (CMC), in which the aliasing of the sideband harmonics generated by the discrete saddle coils is corrected in real time. CMC operation leads to a smoother (i.e. more axisymmetric) boundary. Tearing modes rotate (up to 100 Hz) and partially unlock. Plasma-wall interaction diminishes due to a decrease of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 29 publications
2
61
0
Order By: Relevance
“…The presence of two chains of islands in TEXTOR, compared to only one big island in the RFX edge, is due to the different q profile, and to the unavoidable presence of higher sidebands produced by the ergodic divertor of TEXTOR, as compared to the more sophisticated system of feedback control of RFX-mod, where individual modes can be triggered and sidebands are damped while acting on a single mode. 50 Even if the geometry of the fields in RFX and TEXTOR is different, the results are similar: electrons (energy 30 À 100 eV, depending on radius, and thermal collisions with the background e s tor ¼ 1.5) stick in limited portions of the plasma, with a $3 order of magnitude modulation of L k that retains the geometry of the parent island [see Fig. 5(a)].…”
Section: Test-particle Simulationsmentioning
confidence: 99%
“…The presence of two chains of islands in TEXTOR, compared to only one big island in the RFX edge, is due to the different q profile, and to the unavoidable presence of higher sidebands produced by the ergodic divertor of TEXTOR, as compared to the more sophisticated system of feedback control of RFX-mod, where individual modes can be triggered and sidebands are damped while acting on a single mode. 50 Even if the geometry of the fields in RFX and TEXTOR is different, the results are similar: electrons (energy 30 À 100 eV, depending on radius, and thermal collisions with the background e s tor ¼ 1.5) stick in limited portions of the plasma, with a $3 order of magnitude modulation of L k that retains the geometry of the parent island [see Fig. 5(a)].…”
Section: Test-particle Simulationsmentioning
confidence: 99%
“…The surface q(r rev ) = 0 is called reversal surface and is characterized by rather peculiar transport properties: it has been shown that, due to the resonance of the m = 0 modes, the reversal surface hosts a group of islands with their O and X-points [26] aligned in the toroidal direction at r ≈ r rev which reduce ion transport in the RFP edge (a sort of edge 'transport barrier'). In addition to this, the core of the RFP, especially at high current and with the help of the feedback system of active coils [27], shows the development of a helical equilibrium (single helical axis topology, i.e. SHAx regime) which features an internal transport barrier for electrons [4].…”
Section: Overview Of Density Limit Phenomenologymentioning
confidence: 99%
“…This state has been achieved experimentally in the reversed-field experiment (RFXmod) [10], by increasing the plasma current up to $1:5 MA [11].…”
mentioning
confidence: 93%